1997
DOI: 10.1111/j.1524-4725.1997.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper Lip Reconstruction with Local Island Flap after Neoplasm Excision

Abstract: The healing process was in all the cases but one (partial flap necrosis) free of complications. Follow-up results were also very good functionally and esthetically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Six studies reported outcomes on V-Y advancement flaps with the number of patients ranging from 13 to 109 with a range of upper lip defect locations with and without the involvement of neighboring cosmetic unit borders. [9][10][11][12][13][14] There was a single study on ergotrid flaps for upper lateral lip defects, 15 unspecified rotational flaps for apical triangle defects, 16 melolabial rotational flaps for apical triangle defects, 17 Karapandzic flaps for lateral upper lip defects, 18 alar crescent flaps for central upper lip defects, 19 and propeller facial artery perforator flaps for lateral upper lip defects. 20 Overall, there was significant heterogeneity in the complications as well as functional and aesthetic outcomes reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies reported outcomes on V-Y advancement flaps with the number of patients ranging from 13 to 109 with a range of upper lip defect locations with and without the involvement of neighboring cosmetic unit borders. [9][10][11][12][13][14] There was a single study on ergotrid flaps for upper lateral lip defects, 15 unspecified rotational flaps for apical triangle defects, 16 melolabial rotational flaps for apical triangle defects, 17 Karapandzic flaps for lateral upper lip defects, 18 alar crescent flaps for central upper lip defects, 19 and propeller facial artery perforator flaps for lateral upper lip defects. 20 Overall, there was significant heterogeneity in the complications as well as functional and aesthetic outcomes reported.…”
Section: Resultsmentioning
confidence: 99%
“…Studies examining V-Y advancement flaps, unspecified rotational flaps, melolabial rotational flaps, and propeller facial artery perforator flaps all reported greater than a 90% rate of excellent facial symmetry postoperatively. 14,16,17,20 Patient satisfaction was greater than 90% in all studies that reported this outcome which included studies using V-Y advancement flaps, ergotrid flaps, and propeller facial artery perforator flaps. [13][14][15]20 V-Y advancement flaps in the study by Carvalho and colleagues 9 reported the highest rate of poor scarring with 4 patients (20.0%) where the upper lip defects had no limitations on location and ranged from full-thickness defects involving the vermillion border to defects involving skin and adipose tissue only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles in a recent issue of the journal 1,2 utilize monopedicled island advancement flaps to accomplish reconstructive goals involving the cheek/nose and the upper lip. The authors of the first article 1 state “there is an aesthetic deformity of the island pedicle flap because of trapdooring…,” and Skouge 3 in his commentary on the second article writes that “trapdoor deformities do occur …” using monopedicled island flaps for upper lip reconstruction.…”
mentioning
confidence: 99%
“…The authors of the first article 1 state “there is an aesthetic deformity of the island pedicle flap because of trapdooring…,” and Skouge 3 in his commentary on the second article writes that “trapdoor deformities do occur …” using monopedicled island flaps for upper lip reconstruction. Several authors 2,3 make reference to the absence of subcutaneous tissue in the upper lip, requiring incorporation of orbicularis muscle, ie, a flap which is “myo‐cutaneous in character,” 2 with an incision “down to, and sometimes into, orbicularis.” 3 …”
mentioning
confidence: 99%